Reproductive Biology of Common Carp (Cyprinus carpio) in the 16th of Tishreen Lake (Alkabeer Alshimali River) - حسن, محمود; سلطانه, علي; حماد, بتول (Latakia University Journal -Biological Sciences Series, 2020)
The aim of this search was to study the reproductive biology of common carp Cyprinus carpio in the 16th of Tishreen Lake (Alkabeer Alshimali River). A total of 184 individuals (99 females, 85 males) were collected from three sites (Arshwk, Alsfsaf, Alnahr alaswad) between 13/6/2016 and 26/6/2018 using gill nets and trammel nets. Morphological and morphometric measurements were taken for all individuals; the viscera, gonads and liver were removed; weights were taken and sex was determined.The results showed that the reproductive period occurs between February and May for females and between January and May for males. This was determined according to the Gonado Somatique Index(GSI) which reached (3.58 ± 0.46)% for females in April, with the ovarians weight average (4.94 ± 0.65) g. GSI for males and reached (4.39 ± 0.51)% with an increase in the testicules weight average (4.71 ± 0.98) g in March.The results also showed a good relation between Hepato Somatique Index (HSI)values ​​and both the environmental variations and physiological changes of sexual activity during the reproductive cycle. This index increased when the females start their reproductive season; it reached (0.60 ± 0.01)% in February for females and (0.44 ± 0.04) % In December for males.